Immunization status of Iranian military recruits against Bordetella pertussis infection (whooping cough) - Morteza Izadi; Shahla Afsharpaiman; Nematollah Jonaidi Jafari; Reza Ranjbar; Mohammad Mahdi Gooya; Javad Robat Sarpooshi; Ali Akbar Esfahani; Hamid Soheylipoor (Journal of Infection in Developing Countries)
Introduction: Military recruits are susceptible to respiratory pathogens because of increased antibiotic resistance and the lack of an effective vaccine. The goal of the current study was to determine the immunological status of the Bordetella pertussis among conscripts in Iranian military garrisons.